2007
DOI: 10.1128/jb.01760-06
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of Expression of the Oligopeptide Permease A Proteins of Borrelia burgdorferi

Abstract: burgdorferi will help to identify coregulated proteins that may cooperate to allow the organism to survive in a specific environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 27 publications
3
69
0
1
Order By: Relevance
“…We (17,19) along with others (13,84) have proposed that the poly(T) tracts shared by both bba74 and ospA represent a candidate repressor binding site. ospE is thought to be regulated, in part, by EbfC, a chromosomally encoded YbaB DNA binding protein ortholog (55) induced during tick feeding and murine infection (5,59). The absence of EbfC recognition sites (TGTAACA) within the bba74 upstream region leads us to predict that bba74 and ospE are regulated differently despite the fact that both are downregulated within flat nymphs and induced during the nymphal blood meal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We (17,19) along with others (13,84) have proposed that the poly(T) tracts shared by both bba74 and ospA represent a candidate repressor binding site. ospE is thought to be regulated, in part, by EbfC, a chromosomally encoded YbaB DNA binding protein ortholog (55) induced during tick feeding and murine infection (5,59). The absence of EbfC recognition sites (TGTAACA) within the bba74 upstream region leads us to predict that bba74 and ospE are regulated differently despite the fact that both are downregulated within flat nymphs and induced during the nymphal blood meal.…”
Section: Discussionmentioning
confidence: 98%
“…Seminal studies by Norgard and coworkers (42,83,103) demonstrated that expression of RpoS is regulated by RpoN in concert with the response regulator protein Rrp2. Expression of RpoS, in turn, is essential for the induction of the established virulence factors ospC, dbpBA, and bbk32 as well as numerous other genes thought to be required to establish mammalian infection (18,19,42,59,79,80,100). Analysis of rpoS and RpoS-dependent genes within infected ticks has demonstrated that induction of the RpoS regulon begins during the nymphal blood meal prior to spirochete transmission (i.e., the RpoS-ON state) (19,35,36,39,41,76,77).…”
mentioning
confidence: 99%
“…Similarly, many B. burgdorferi genes encoding proteins with various putative physiological functions were induced by Rrp2, RpoN and RpoS; these genes included bb0251 (leuS), bb0777 (apt), bbk17 (adeC), bb0257 (cell division), bb0842 (arcB), bb0329 (oppA-2), bba34 (oppAV), bb0313 (ftsJ), bb0797 (mutS), bb0637 (nhaC-1), bbd20 (transposase), bb0646 (hydrolase), bb0728 (nox) and bb0729 (gltP) (Fraser et al, 1997). Among these genes, bb0329 and bba34 encode two putative periplasmic oligopeptide-binding proteins, which facilitate the transport of small peptides and essential amino acids (Fraser et al, 1997;Medrano et al, 2007). In addition, bb0728 and bb0729 are presumed to form an operon involved in the uptake of the amino acid glutamate (Fraser et al, 1997).…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
“…BpaB and EbfC compete with each other for binding to erp operator DNA (13). Like the erp genes, ebfC is poorly expressed in unfed ticks but significantly induced during tick feeding and during mammalian infection (44). For the present work, independent in vivo and in vitro studies were performed to determine the effects of these two proteins on Erp expression.…”
mentioning
confidence: 99%